Prevalence and Antibiotic Resistance Pattern of Methicillin-Resistant Staphylococcus aureus Isolated from Iraqi Hospitals - H Sami Awayid; S Qassim Mohammad (Archives of Razi Institute, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) bacteria are often multi-drug resistant, resulting in a high rate of treatment failure. This study aimed to identify the antibiotics resistance profile and molecular characteristics of MRSA strains isolated from patients' samples, including skin, wounds, and burns, which are the most common infections, and collected from hospitals. The samples included 34 MRSA isolates gathered from January 2020 to September 2020. All isolates were tested using the Kirby-Bauer method to determine MRSA susceptibility against antibiotics using the minimum inhibitory concentration protocol and the E-test. The polymerase chain reaction was used for the detection of antibiotic resistance genes, including tetracycline, erythromycin, linezolid, gentamicin, rifampicin, ciprofloxacin, quinupristin-dalfopristin, clindamycin, and mecA. Staphylococcal Cassette Chromosome mec (SCCmec) was determined by multilocus sequence typing of all isolates; accordingly, the findings indicated that the sensitivity of linezolid, quinupristin-dalfopristin, rifampin, daptomycin, and vancomycin differed. Moreover, multidrug resistance of MRSA was shown to be more than 90% for penicillin and 91.1% for erythromycin. It was revealed that SCCmec III was resistant to at least four to five different antibiotics. ST585 (2.9%), ST240 (8.8%), ST45 (14.7%), ST22 (17.6%), and ST239 (higher rate) were the five sequence types found in STs (55.8%). Finally, it was indicated that the emergence of MRSA in these Iraqi hospitals highlighted further research to better understand how the infection might be effectively controlled.